Niobium-doped manganese vanadium sodium phosphate / carbon composite material as well as preparation method and application thereof

By doping niobium elements into the positive electrode material of Na4MnV (PO4)3 of the sodium ion battery to form a niobium-doped manganese vanadium sodium/carbon composite material, the poor electronic conductivity and Jahn-Teller distortion problems of NMVP are solved, and high cycle stability and excellent rate performance are achieved.

CN119833627APending Publication Date: 2025-04-15武汉启钠新能源科技有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411982982.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The sodium ion battery positive electrode material Na4MnV(PO4)3 (NMVP) has poor electronic conductivity and Jahn-Teller distortion problems, which limits its cyclic stability and rate performance.

Method used

By doping niobium elements into the manganese vanadium sodium phosphate system, a niobium-doped manganese vanadium sodium phosphate/carbon composite material is formed, the redox reaction path of the material is optimized, the diffusion rate of sodium ions is improved, and the uniform distribution of Nb elements is ensured through a high-temperature calcination process.

Benefits of technology

The high cycle stability and excellent rate performance of the material are achieved, the volume changes during the charging and discharging process are reduced, and the energy density and charging rate of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005221938090000011
    Figure HDA0005221938090000011
  • Figure HDA0005221938090000012
    Figure HDA0005221938090000012
  • Figure HDA0005221938090000021
    Figure HDA0005221938090000021
Patent Text Reader

Abstract

The invention discloses a niobium-doped sodium vanadium manganese phosphate / carbon composite material, which is a composite material formed by niobium-doped sodium vanadium manganese phosphate and carbon, the stoichiometric formula of niobium-doped sodium vanadium manganese phosphate is Na < 4-3x > Mn < 1-x > Nb < x > V (PO4) 3, and x is more than or equal to 0.01 and less than or equal to 0.06. The preparation method comprises the following steps: reacting a vanadium source with a complexing agent, introducing a manganese source, a niobium source, a sodium source, a phosphorus source and a carbon source, compounding by adopting a sol-gel method, and carrying out high-temperature calcination to obtain the niobium-doped manganese vanadium sodium phosphate / carbon composite material, so that a stable crystal structure can be formed, and the volume change in the charge-discharge process is reduced; the redox reaction path of the obtained material is optimized, and the diffusion rate of sodium ions is increased; when being used as a sodium-ion battery positive electrode material, the lithium ion battery positive electrode material can show excellent rate capability and high cycling stability under large current; the preparation method is simple, short in period and suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical energy materials, and in particular relates to a sodium ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of renewable energy, the demand for efficient energy storage technology has increased dramatically. For a long time, lithium-ion batteries have dominated the field of energy storage with their excellent performance, but their large-scale application has also caused problems such as lithium resource depletion and rising costs. In this context, metallic sodium, as a potential alternative material, has attracted much attention due to its advantages such as abundant resources, low cost, and environmental friendliness. Sodium-ion batteries show great application potential in the field of energy storage, but key issues such as their relatively low operating voltage, the need to improve cycle life and stability, and the need to optimize energy density and charging rate remain to be resolved.

[0003] Sodium superion conductor (NASICON) type polyanion compound Na 3 V 2 (PO 4 ) 3 (NVP) has attracted attention due to its advantages such as high ionic conductivity, good theoretical capacity and voltage platform, but it still has limitations such as high cost of vanadium, environmental impact and relatively low working voltage. 4 MnV(PO 4 ) 3 (NMVP) has a higher operating voltage (3.6V) and a 35% lower cost than NVP. It shows two clear voltage platforms in the 2.5-3.8V voltage window and is a very promising cathode material for sodium ion batteries. However, NMVP still has some key issues: 1) The VO 6 / MnO 6 Octahedron is PO 4 The tetrahedrons are separated, which makes it impossible to form an effective continuous electron conduction path, resulting in poor electronic conductivity; 2) During the charge and discharge cycle, the active Mn in NMVP 3+ Ions will experience the Jahn-Teller effect, causing lattice distortion and showing significant polarization, which severely limits its cycle stability and rate performance. In order to solve the problems of low electronic conductivity and Jahn-Teller distortion, carbon coating and doping are the most effective strategies for NMVP positive electrodes. In particular, doping modification of NMVP has significant potential in improving battery performance, but it still faces limitations in doping modification technology, insufficient material performance and stability, and other issues. Summary of the invention

[0004] The main purpose of the present invention is to provide a niobium-doped sodium manganese vanadium phosphate / carbon composite material in view of the problems and shortcomings of the prior art, which can form a stable crystal structure, reduce the volume change occurring during the charge and discharge process, optimize the redox reaction path of the obtained material, and increase the diffusion rate of sodium ions; when used as a positive electrode material for a sodium ion battery, it can exhibit excellent rate performance and high cycle stability under high current.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A niobium-doped sodium manganese vanadium phosphate / carbon composite material, which is a composite material formed by niobium-doped sodium manganese vanadium phosphate and carbon, wherein the stoichiometric formula of the niobium-doped sodium manganese vanadium phosphate is Na 4-3x Mn 1-x Nb x V(PO 4 ) 3 , 0.01≤x≤0.06; the niobium element is evenly distributed in the sodium manganese vanadium phosphate phase.

[0007] Furthermore, the niobium-doped sodium manganese vanadium phosphate / carbon composite material has a porous structure formed by the accumulation of nanoparticles.

[0008] The preparation method of the above-mentioned niobium-doped sodium manganese vanadium phosphate / carbon composite material comprises the following steps: firstly, the vanadium source is evenly dispersed in water, a complexing agent is added under heating and stirring, and after sufficient reaction, a manganese source, a niobium source, a sodium source, a phosphorus source and a carbon source are added in sequence, and the mixture is heated and stirred to a gel state, and then ground to obtain a powdery precursor after drying, and finally calcined at high temperature to obtain the niobium-doped sodium manganese vanadium phosphate / carbon composite material.

[0009] In the above scheme, the molar ratio of V introduced from the vanadium source, Mn introduced from the manganese source, Nb introduced from the niobium source, Na introduced from the sodium source, and P introduced from the phosphorus source is 1:1-x:x:4-3x:3, 0.1≤x≤0.6.

[0010] In the above scheme, the molar ratio of the vanadium source to the carbon source is 2:1-6.

[0011] In the above scheme, the complexing agent can be oxalic acid or the like.

[0012] In the above scheme, the molar ratio of the vanadium source to the complexing agent is 1:2-4.

[0013] In the above scheme, the vanadium source can be selected from at least one of vanadyl sulfate, vanadium pentoxide, ammonium metavanadate, etc.

[0014] In the above scheme, the manganese source can be selected from at least one of manganese acetate, manganese oxalate, manganese carbonate, etc.

[0015] In the above scheme, the niobium source can be selected from at least one of niobium pentoxide, niobium oxalate, niobium carbide, ammonium niobate oxalate hydrate, and the like.

[0016] In the above scheme, the sodium source can be selected from at least one of sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, etc.

[0017] In the above scheme, the phosphorus source can be selected from at least one of ammonium dihydrogen phosphate, sodium dihydrogen phosphate, phosphoric acid, etc.

[0018] In the above scheme, the carbon source can be selected from at least one of sucrose, citric acid, glucose, polyethylene glycol, thiourea and the like.

[0019] In the above scheme, the temperature of the heating and stirring reaction is 50-150°C and the time is 1-5h.

[0020] In the above scheme, the calcining equipment is a tubular furnace.

[0021] In the above scheme, the atmosphere used in the calcination step is N 2 or N 2 / H 2 .

[0022] Furthermore, the N 2 / H 2 Medium H 2 The content is 4 to 6 vol%.

[0023] In the above scheme, the temperature used in the high temperature calcination step is 300-800°C and the time is 3-10h.

[0024] The present invention first reacts a vanadium source with a complexing agent, then introduces a manganese source, a niobium source, a sodium source, a phosphorus source and a carbon source to compound by a sol-gel method, and then performs high-temperature calcination to obtain a niobium-doped sodium manganese vanadium phosphate / carbon composite material. The present invention adds niobium elements to the sodium manganese vanadium phosphate system to form a strong niobium-oxygen bond, which can promote the stability of the crystal structure of the material, play a role similar to a pillar, inhibit structural collapse, and reduce the volume change during the charge and discharge process; the doping of high-valent niobium ions can also guide the generation of sodium vacancies and increase the diffusion rate of sodium ions, which helps to speed up the charge and discharge speed of the battery and improve the rate performance. In addition, Nb 5+ The substitution can optimize the redox reaction path of the material, promote the redox reaction, and help improve the capacity and energy density of the battery. Specifically, it can exhibit excellent rate performance and high cycle stability under large current.

[0025] The present invention adopts vanadium source complexation, sol-gel and high-temperature calcination processes, which can effectively promote the uniform distribution of Nb elements in the sodium manganese vanadium phosphate positive electrode material, and ensure the repeatability and high efficiency of the doping process.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1) The niobium-doped sodium manganese vanadium phosphate / carbon composite material of the present invention adopts a vanadium source complexation and a preparation and composite process combined with sol-gel and high-temperature calcination, which can promote the efficient doping and uniform distribution of the Nb element in the sodium manganese vanadium phosphate positive electrode material, and can realize the controllable adjustment of the content of the Nb element in the crystal structure;

[0028] 2) The niobium-doped sodium manganese vanadium phosphate / carbon composite material of the present invention has high electrical conductivity; Nb is introduced into the Mn site in the sodium manganese vanadium phosphate. 5+ , where Nb 5+ It has a larger ionic radius and can expand the lattice parameters. High-valent ion doping can guide the system to produce vacancies, change the electrochemical active sites of NMVP, optimize the migration path of sodium ions, help sodium ions migrate faster in the crystal structure, accelerate the diffusion and storage of sodium ions, increase the reversible specific capacity, reduce polarization, and improve the charge and discharge efficiency of the battery.

[0029] 3) The niobium-doped sodium manganese vanadium phosphate / carbon composite material of the present invention has high stability; the incorporated Nb has a high binding energy with O, which helps to inhibit oxygen precipitation during the sodium removal process, thereby improving the crystal structure stability of the material, reducing the performance degradation caused by lattice changes during the charge and discharge process, and improving the cycle stability and service life of the battery.

[0030] 4) The preparation process involved in the present invention is simple and the preparation cycle is short, which meets the requirements of energy conservation, emission reduction and green chemistry. The product has a high laboratory-level daily output, which is conducive to the large-scale application of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 (a) low magnification and (b) high magnification scanning electron microscope images of the niobium-doped sodium manganese vanadium phosphate / carbon composite material prepared in Example 4 of the present invention.

[0032] Figure 2 The X-ray diffraction patterns of the niobium-doped sodium manganese vanadium phosphate / carbon composite materials prepared in Example 4 of the present invention and Comparative Example 1 are shown.

[0033] Figure 3 This is a rate performance diagram of the niobium-doped sodium manganese vanadium phosphate / carbon composite material prepared in Example 4 of the present invention and Comparative Example 1.

[0034] Figure 4 This is a long cycle stability performance diagram of the niobium-doped sodium manganese vanadium phosphate / carbon composite material prepared in Example 4 of the present invention and Comparative Example 1 at a 5C rate.

[0035] Figure 5This is a long cycle stability performance diagram of the niobium-doped sodium manganese vanadium phosphate / carbon composite material prepared in Example 4 of the present invention and Comparative Example 1 at a rate of 20C. DETAILED DESCRIPTION

[0036] The technical solutions adopted in the present invention are described in detail below through specific implementation examples, which are only part of the present invention and do not represent all embodiments. Unless otherwise specified, the experimental methods adopted in the present invention are all conventional methods, and the instruments and equipment adopted are all commercial products in the field of this technology.

[0037] Example 1

[0038] A niobium-doped sodium manganese vanadium phosphate / carbon composite material, the preparation method of which comprises the following steps:

[0039] 1) 0.01 mol V 2 O 5 Evenly dispersed in 40 ml of deionized water to obtain a yellow solution, then 0.03 mol of oxalic acid (H 2 C 2 O 4 ), so that V 5+ Restore to V 4+ , until the solution turns clear blue, then add 0.0194 mol Mn(CH 3 COO 2 、0.0003mol Nb 2 O 5 、0.06mol NH 4 H 2 PO 4 , 0.0391mol Na 2 CO 3 and 1.2 g sucrose to obtain a turbid blue solution, which was heated (maintained at 80 °C) and stirred until it reached a gel state;

[0040] 2) placing the gel obtained in step 1) in an oven at 80° C. and drying for 24 h to obtain a blue block solid, which was then ground to obtain a light blue powder precursor;

[0041] 3) placing the powder obtained in step 2) in a tube furnace at N 2 / H 2 (H 2 The calcination is carried out in an atmosphere with a content of 5 vol%), and the specific steps are: heating to 750°C at a heating rate of 10°C / min, and keeping the temperature for 9 hours to obtain the niobium-doped sodium manganese vanadium phosphate / carbon composite material.

[0042] Example 2

[0043] A niobium-doped sodium manganese vanadium phosphate / carbon composite material, the preparation method of which comprises the following steps:

[0044] 1) 0.01 mol V 2 O 5 Evenly dispersed in 40 ml of deionized water to obtain a yellow solution, then 0.03 mol of oxalic acid (C 6 H 8 O 7 ), so that V 5+ Restore to V 4+ , until the solution turns clear blue, then add 0.0194 mol Mn(CH 3 COO 2 0.0006mol C 4 H 4 nnJC 9 ·nH 2 O (molecular weight is 302.98, the same below), 0.06 mol NH 4 H 2 PO 4 , 0.0391mol Na 2 CO 3 and 3.648 mg of sucrose to obtain a turbid blue solution, which was heated (maintained at 80°C) and stirred until it reached a gel state;

[0045] 2) placing the gel obtained in step 1) in an oven at 80° C. and drying for 24 h to obtain a blue block solid, which was then ground to obtain a light blue powder precursor;

[0046] 3) placing the powder obtained in step 2) in a tube furnace at N 2 The calcination is carried out in an atmosphere of, specifically, the steps are: heating to 750° C. at a heating rate of 10° C. / min, and keeping the temperature for 9 hours to obtain the niobium-doped sodium manganese vanadium phosphate / carbon composite material.

[0047] Example 3

[0048] A niobium-doped sodium manganese vanadium phosphate / carbon composite material, the preparation method of which comprises the following steps:

[0049] 1) 0.01 mol V 2 O 5 Evenly dispersed in 40 ml of deionized water to obtain a yellow solution, then 0.03 mol of oxalic acid (H 2 C 2 O 4 ), so that V 5+ Restore to V 4+, until the solution turns clear blue, then add 0.0194 mol Mn(CH 3 COO 2 0.0006mol C 4 H 4 nnJC 9 ` n 2 O, 0.06 mol NH 4 H 2 PO 4 、0.0391molNa 2 CO 3 and 1.2 g of glucose to obtain a turbid blue solution, which was heated (maintained at 80 °C) and stirred until it reached a gel state;

[0050] 2) placing the gel obtained in step 1) in an oven at 80° C. and drying for 24 h to obtain a blue block solid, which was then ground to obtain a light blue powder precursor;

[0051] 3) placing the powder obtained in step 2) in a tube furnace at N 2 The calcination is carried out in an atmosphere of, specifically, the steps are: heating to 750° C. at a heating rate of 10° C. / min, and keeping the temperature for 9 hours to obtain the niobium-doped sodium manganese vanadium phosphate / carbon composite material.

[0052] Example 4

[0053] A niobium-doped sodium manganese vanadium phosphate / carbon composite material, the preparation method of which comprises the following steps:

[0054] 1) 0.01 mol V 2 O 5 Evenly dispersed in 40 ml of deionized water to obtain a yellow solution, then oxalic acid (H 2 C 2 O 4 ), so that V 5+ Restore to V 4+ , until the solution turned into a clear blue, followed by the addition of 0.0194 mol Mn(CH 3 COO 2 0.0006mol C 4 H 4 nnJC 9 ` n 2 O, 0.06 mol NaH 2 PO 4 , 0.0091mol Na 2 CO 3and 1.2 g sucrose and polyethylene glycol (PEG) (the mass ratio of sucrose to PEG is 2:1) to obtain a turbid blue solution, which is then heated (maintained at 80°C) and stirred until it reaches a gel state;

[0055] 2) placing the gel obtained in step 1) in an oven at 80° C. and drying for 24 h to obtain a blue block solid, which was then ground to obtain a light blue powder precursor;

[0056] 3) placing the powder obtained in step 2) in a tube furnace at N 2 The calcination is carried out in an atmosphere of, specifically, the steps are: heating to 750° C. at a heating rate of 10° C. / min, and keeping the temperature for 9 hours to obtain the niobium-doped sodium manganese vanadium phosphate / carbon composite material.

[0057] Comparative Example 1

[0058] A sodium manganese vanadium phosphate composite material, the preparation method of which is different from that of Example 4 in that no C is added 4 H 4 nnJC 9 ` n 2 O, the specific preparation method comprises the following steps:

[0059] 1) 0.01 mol V 2 O 5 Evenly dispersed in 40 ml of deionized water to obtain a yellow solution, then 0.03 mol C was added under continuous heating and stirring at 80 °C. 6 H 8 O 7 , so that V 5+ Restore to V 4+ , until the solution turned into a clear blue, followed by the addition of 0.02 mol Mn(CH 3 COO 2 , 0.06 mol NaH 2 PO 4 , 0.01mol Na 2 CO 3 and 1.2 g sucrose to obtain a turbid blue solution, which was heated (maintained at 80 °C) and stirred until it reached a gel state;

[0060] 2) placing the gel obtained in step 1) in an oven at 80° C. and drying for 24 h to obtain a blue block solid, which was then ground to obtain a light blue powder precursor;

[0061] 3) placing the powder obtained in step 2) in a tube furnace at N 2 / H 2 The calcination is carried out in an atmosphere of, specifically, the steps are: heating to 750°C at a heating rate of 10°C / min, and keeping the temperature for 9 hours to obtain the sodium manganese vanadium phosphate / carbon composite material.

[0062] Comparative Example 2

[0063] A niobium-doped sodium manganese vanadium phosphate composite material, the preparation method of which is different from that of Example 4 in that the carbon source is changed, sucrose and PEG are replaced with urea, and the specific preparation steps include:

[0064] 1) 0.01 mol V 2 O 5 Evenly dispersed in 40 ml of deionized water to obtain a yellow solution, then 0.03 mol C was added under continuous heating and stirring at 80 °C. 6 H 8 Oxalic acid (H 2 C 2 O 4 ), so that V 5+ Restore to V 4+ , until the solution turned into a clear blue, followed by the addition of 0.0194 mol Mn(CH 3 COO 2 , 0.0006mol C 4 H 4 nnJC 9 ` n 2 O, 0.06 mol NaH 2 PO 4 , 0.01 mol mol Na 2 CO 3 and 1.2 g of urea to obtain a turbid blue solution, which was heated (maintained at 80 ° C) and stirred until it reached a gel state;

[0065] 2) placing the gel obtained in step 1) in an oven at 80° C. and drying for 24 h to obtain a blue block solid, which was then ground to obtain a light blue powder precursor;

[0066] 3) placing the powder obtained in step 2) in a tube furnace at N 2 / H 2 The calcination is carried out in an atmosphere of, specifically, the steps are: heating to 750°C at a heating rate of 10°C / min, and keeping the temperature for 9 hours to obtain the sodium manganese vanadium phosphate / carbon composite material.

[0067] Comparative Example 3

[0068] A niobium-doped sodium manganese vanadium phosphate composite material, the preparation method of which is different from that of Example 4 in that the complexing agent is changed from oxalic acid to citric acid, and the specific preparation steps include:

[0069] 1) 0.01 mol V 2 O 5Evenly dispersed in 40 ml of deionized water to obtain a yellow solution, then 0.03 mol of citric acid (C 6 H 8 O 7 ), so that V 5+ Restore to V 4+ , until the solution turns clear blue, then add 0.0194 mol Mn(CH 3 COO 2 0.0006mol C 4 H 4 nnJC 9 ` n 2 O, 0.06 mol NaH 2 PO 4 、0.01molNa 2 CO 3 and 3.648 mg of sucrose to obtain a turbid blue solution, which was heated (maintained at 80°C) and stirred until it reached a gel state;

[0070] 2) placing the gel obtained in step 1) in an oven at 80° C. and drying for 24 h to obtain a blue block solid, which was then ground to obtain a light blue powder precursor;

[0071] 3) placing the powder obtained in step 2) in a tube furnace at N 2 The calcination is carried out in an atmosphere of, specifically, the steps are: heating to 750° C. at a heating rate of 10° C. / min, and keeping the temperature for 9 hours to obtain the niobium-doped sodium manganese vanadium phosphate / carbon composite material.

[0072] Compared with Example 4, Comparative Example 1 is not doped with Nb 5+ The carbon source of Comparative Example 2 is changed from sucrose and PEG mixture to urea, and the complexing agent oxalic acid is changed to citric acid in Comparative Example 3. The rate performance and cycle stability of the materials prepared in Comparative Examples 2-3 are poor, with a small reversible specific capacity, poor conductivity and sodium ion diffusion kinetics compared with Example 4, and the performance is similar to that of Comparative Example 1. The microscopic morphology of the product niobium doped sodium manganese vanadium phosphate / carbon positive electrode material obtained in Example 4 is shown in Figure 1 The obtained product is an irregular block-shaped porous structure formed by the accumulation of nanoparticles. The XRD pattern of the product obtained in Example 4 is as follows Figure 2 As shown, it can be seen that the diffraction pattern exhibited by the obtained product corresponds to the R3'c space group and the NASICON structure (JCDS 70-3613), and there is no impurity phase, confirming the successful synthesis of niobium-doped sodium manganese vanadium phosphate / carbon positive electrode material.

[0073] The niobium-doped sodium vanadium phosphate / carbon positive electrode material (active material) prepared in Example 4 was used to assemble a half-cell, and the specific steps included: fully mixing and dispersing the active material, Super P and binder polyvinylidene fluoride (PVDF) at a mass ratio of 85:10:5 to form a uniform slurry, and then evenly coating the obtained slurry on an aluminum foil, and drying the electrode in a vacuum drying oven at 80°C; cutting the obtained electrode into an electrode sheet with a diameter of 12 mm for standby use, and the active material loading of the obtained electrode sheet was 2-3 mg cm -2 ; Sodium metal and glass fiber diaphragm (GF / D) were used as counter electrode and diaphragm, respectively, and the electrolyte contained 1.0 mol L -1 NeA 6 The solution is composed of 100% polycarbonate solvent and 5% fluoroethylene carbonate. The prepared electrode sheet is used as the positive electrode and assembled into a button-type sodium ion battery using a LIR2032 battery shell.

[0074] The obtained button-type sodium ion battery was tested for rate performance in the voltage range of 2.5 to 3.8 V. The results are shown in Figure 3 It can be seen that the sample obtained in Example 4 exhibits a capacity of 100.25 mAh g at 1C. -1 The discharge capacity of the first cycle is 97.6%, which is better than that of the comparative example 1 (94.8 mAh g -1 , 96.2%); In addition, constant current charge and discharge tests were carried out at 2C, 5C, 10C and 20C rates, and the discharge specific capacities of the samples obtained in Example 4 were 98.4 mAh g -1 , 96.5mAh g -1 , 94.7mAhg -1 , 91.7mAh g -1 and 86.8mAh g -1 , showing excellent rate performance. Obviously better than comparative example 1 (94.8 mAh g -1 , 90.6mAh g -1 , 85.7mAh g -1 , 78.5mAh g -1 , 67.9mAh g -1 ; corresponding to 2C, 5C, 10C, 20C). At 1C current density ( Figure 4 ), the first cycle discharge capacity of the sample obtained in Example 4 is as high as 95.5 mAh g -1 After 400 cycles, the discharge capacity is 85.9 mAh g -1 , the capacity retention rate is 89.9%, which is better than the capacity retention rate of comparative example 1 (67.3). Figure 5), Example 4 achieved 65.7 mAh g after 1000 cycles at 10C. -1 The stable charging capacity of the battery is 76.8% of the initial cycle, which is better than that of Comparative Example 1 in terms of capacity retention and cycle stability.

[0075] The above properties indicate that the prepared niobium-doped sodium manganese vanadium phosphate / carbon composite material has excellent rate capability and cycle performance, and is an ideal material for realizing high-power and long-life sodium-ion batteries.

[0076] Finally, it should be noted that the technical solutions implemented above are examples, which are only used to illustrate the technical solutions of this article, rather than to limit them. For those of ordinary skill in the art, they can still make modifications and replacements based on the examples, which obviously belong to the protection scope of the present invention. The present invention is not limited to the above-mentioned embodiments, but also has many other variations. According to the technical essence of the present invention, simple modifications and changes to the embodiments are made, without departing from the technical solution ideas of the present invention, and are all described in the protection scope of the present invention.

Claims

1. A niobium-doped sodium manganese vanadium phosphate / carbon composite material, characterized in that: It is a composite material formed by niobium-doped sodium manganese vanadium phosphate and carbon, wherein the stoichiometric formula of niobium-doped sodium manganese vanadium phosphate is Na 4-3x Mn 1-x Nb x V(PO4)3, 0.01≤x≤0.

06.

2. The niobium-doped sodium manganese vanadium phosphate / carbon composite material according to claim 1, characterized in that: The niobium-doped sodium manganese vanadium phosphate / carbon composite material has a porous structure formed by the accumulation of nanoparticles.

3. The method for preparing the niobium-doped sodium manganese vanadium phosphate / carbon composite material according to claims 1 to 2, characterized in that: The following steps are involved: First, the vanadium source is evenly dispersed in water, and a complexing agent is added under heating and stirring. After sufficient reaction, a manganese source, a niobium source, a sodium source, a phosphorus source and a carbon source are added in sequence, and the mixture is heated and stirred to a gel state. After drying, the mixture is ground to obtain a powdery precursor, and finally high-temperature calcination is performed to obtain the niobium-doped sodium manganese vanadium phosphate / carbon composite material.

4. The preparation method according to claim 3, characterized in that: The molar ratio of V introduced from the vanadium source, Mn introduced from the manganese source, Nb introduced from the niobium source, Na introduced from the sodium source, and P introduced from the phosphorus source is 1:1-x:x:4-3x:3, 0.1≤x≤0.

6.

5. The preparation method according to claim 3, characterized in that: The molar ratio of the vanadium source to the carbon source is 2:1-6; the molar ratio of the vanadium source to the complexing agent is 1:2-4.

6. The preparation method according to claim 3, characterized in that: The complexing agent is oxalic acid.

7. The preparation method according to claim 3, characterized in that: The vanadium source is at least one of vanadyl sulfate, vanadium pentoxide, and ammonium metavanadate; the manganese source is at least one of manganese acetate, manganese oxalate, and manganese carbonate; the niobium source is at least one of niobium pentoxide, niobium oxalate, niobium carbide, and ammonium niobate oxalate hydrate; the sodium source is at least one of sodium carbonate, sodium bicarbonate, and sodium dihydrogen phosphate; the phosphorus source is at least one of ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and phosphoric acid; and the carbon source is at least one of sucrose, citric acid, glucose, polyethylene glycol, and thiourea.

8. The preparation method according to claim 3, characterized in that: The heating and stirring reaction is carried out at a temperature of 50-150° C. and for a time of 1-5 h.

9. The preparation method according to claim 3, characterized in that: The high temperature calcination step adopts a temperature of 300-800° C. and a time of 3-10 hours.

10. Use of the niobium-doped sodium manganese vanadium phosphate / carbon composite material according to claim 1 or 2 or the niobium-doped sodium manganese vanadium phosphate / carbon composite material prepared by the preparation method according to any one of claims 3 to 9 in sodium ion batteries.